Math Problem

emmaiskool242

Junior Member
I'm using the distance formula, its d=the square root of (x of 2-x of 1)2{squared} + ( y of 2 - y of 10 2{ squared} and I am supposed to plug in the points (3{=x of 1},3/7{=y of 1})(4{=x of 2},-2/7{=y of2}) and I'm supposed to figure out what D equals. I don't know if you can figure that out but please try and help me. ~THANKS

soroban

Elite Member
Hello, emmaiskool242!

I think I figured out what you're saying . . .

I'm using the distance formula: $$\displaystyle \,D\:=\:\sqrt{(x_2-x_1)^2\,+\,(y_2-y_1)^2}$$

I am supposed to plug in the points $$\displaystyle \left(3,\,\frac{3}{7}\right)$$ and $$\displaystyle \left(4,-\frac{2}{7}\right)$$

and I'm supposed to figure out what $$\displaystyle D$$ equals.
$$\displaystyle \;\;$$You don't understand where the numbers go?
$$\displaystyle \;\;$$You can't handle fractions?
$$\displaystyle \;\;$$A square root gives you brain-freeze?

Try to "read" the Distance Formula.
Under the square root, it says:
$$\displaystyle \;\;$$Subtract the two x-values ... and square.
$$\displaystyle \;\;$$Subtract the two y-values ... and square.
$$\displaystyle \;\;$$Add the two quantities
$$\displaystyle \;\;$$Take the square root.

We have: $$\displaystyle \\:=\:\sqrt{(4 - 3)^2\,+\,\left(-\frac{2}{7}\,-\,\frac{3}{7}\right)^2} \:= \:\sqrt{1^2\,+\,\left(-\frac{5}{7}\right)^2}\:=\:\sqrt{1\,+\,\frac{25}{49}} \:=\:\sqrt{\frac{74}{49}}$$

Therefore: $$\displaystyle \,D\:=\:\frac{\sqrt{74}}{\sqrt{49}}\:=\:\frac{\sqrt{74}}{7}$$

emmaiskool242

Junior Member
Yes thats what I was saying and fractions just aren't my thing.....Thankyou for your help,and I will keep trying =)